The Impact of Transformational Leadership and Job Characteristics on Employee Engagement In Bank BRI KC Boulevard Manado - Dian Artanti; Joy E. Tulung; Lawren J. Rumokoy (Universitas Sam Ratulangi, 2023)
This research aims to analyze the impact of transformational leadership and job characteristics on employee engagement in Bank Rakyat Indonesia, Manado boulevard branch office. This study uses quantitative methods. the data collection method by a questionnairemeasured with the Likert scale method given to 30 respondents that works in Bank BRI KC Manado Boulevard. The analytical tool used is Multiple Linear Regression by using the SPSS Program. The results of this study indicate that transformational leadership and job characteristics have a positive influence on employee engagement in PT. Bank Rakyat Indonesia, Manado Boulevard branch, The transformational leadership variable has a positive effect on employee engagement, and job characteristics have no effect on employee engagement.